PELATIHAN KEPUASAN KERJA DAN KOMITMEN ORGANISASI DI RSNU TUBAN - eva silviana rahmawati; Miftahul Munir; Muhammad Sudrajat (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
The research aims to determine the effect of Job Satisfaction, Organizational Commitment and Job Stress partially or simultaneously on intention to leave at RS Nahdlatul Ulama Tuban. The research uses quantitative causal and associative approach. The sample amounted to 92 people. Determination of the sample in this study using the method of saturated sampling. Gathering data using questionnaires and interviews, while the analysis of data using multiple linear regression analysis. Research at a significance level of 5% showed that: 1) t test result on job satisfaction variable is -2.162 with a significance value of 0.033. It means job satisfaction has a negative and significant influence on intention to leave. 2) t test on organizational commitment variabel is -2.333 with a significance value of 0.022. It means organizational commitment has a negative and significant influence on intention to leave. 3) t test on job stress variable is 2.241 with a significant value of 0.021. it means job stress has a positive and significant influence on intention to leave. 4) Determination coefficient test (R2) for X1, X2 and X3 is 0.234, it means intention to leave can be influenced by job satisfaction, organizational commitment and job stress around 23,4% , then other factors around 76,6%. Key word: Job Satisfaction, Organizational Commitment, Job Stress and Intention to Leave